UNDERSTANDING OF INTERLINGUAL TRANSLATION "DI ATAS" BY AGRIBUSINESS STUDENTS IN PROGRAM OF ENGLISH AS GENERAL COURSE STUDY - Allif Syahputra Bania; Rahmiati Rahmiati; Muhammad Yakob (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Translation learning is one of the main focuses in language learning and teaching activities in the English class in the agribusiness study program at the University of Samudra so that consciously or unconsciously students have taken the action of translating between Indonesian and English. This study wants to see the ability of bilingual translation with respect to the word 'di atas' which is translated from Indonesian to English. The interlingual translation of the word 'di atas' results in several products of translating into English such as the preposition 'on', 'above' and 'over'. Starting from the same source language but after being translated into English, the three interlingual translation products have almost the same function and but not the same thing. This research method is a test method with a quantitative descriptive approach given through the Whatspp application because the Covid-19 pandemic is still ongoing until this research is worked on. The research object was 32 students with a time limit given to answer the test is 15 minutes. With the dominance of the student's success in answering the test correctly and the success rate being above 50% or half of the total number of research objects, the student's ability to answer the test correctly to the interlingual translation problem in this study is good. Likewise, from the questionnaire data obtained as many as 59% of students who translate interlingually 'di atas’ into over, it can be concluded that students are good at understanding the function of the prepositions given in the test questions.